A systematic review of studies on body and politics in contemporary Iran - M.S. Zokaei; M. Amanpour (Interdisciplinary Studies in the Humanities, 2024)
From the Naserite era until now, the body has always been the issue of disputes, conflicts and competition between social groups, political parties and different discourses in Iran. Despite this, studies of the body, in general, the relationship between the political system and the body in Iran, in particular, is a new domain that has not received serious attention from academic circles in the country. The present article is a systematic review of the researches accomplished in this field over the last two decades. Such a study, in addition to providing an analysis of approaches, methods, issues, and findings of these studies, and reviewing the weaknesses and strengths of the existing research, can identify the neglected fields in this domain and lead to a deeper understanding of the issue of the body as a social and political construct in the contemporary Iranian society. As such, relying on the analysis of the content and themes of the available sources, we are looking for a systematic analysis of the problematic, study tradition and methodology of these studies. The findings show that the most basic problem of these researchers is to study the role and place of the body in the process of nation building and modernity in Iran, or the body as a factor of conflict between power (political sovereignty) and Iranian social groups and activists. Also, the tradition of sociology with two theoretical approaches, post-structuralist and structuralist, can be considered as the dominant approach in the studies of politics and the body in Iranian social sciences during the last two decades..